The Accuracy of TIAC Calculated Using SPECT/CT Imaging Data at 36- and 100-Hours Post Injection and Prior Information in 177Lu-DOTATATE - Siyami, Rizka Mutik; Sri Oktamuliani; M. Dlorifun Naqiyyun; Intan Apriliani Syaridatul Mu'minah (Jurusan Fisika FMIPA Universitas Andalas, 2024)
In internal radionuclide therapy, there is a growing demand for streamlined methods that alleviate the measurement burden on patients and reduce the associated costs of individual dosimetry. This study assessed the precision of the Two Time Point Dosimetry (2TPD) model, a data-efficient approach, compared to the well-established All Time Point Dosimetry (ATPD) model. The investigation involved the analysis of time-activity data collected from the kidneys of seven patients who were administered 177Lu-DOTATATE and underwent SPECT/CT imaging (PMID 3344306). Data points were specifically gathered at the 36-hour and 100-hour post-injection marks. Employing prior information, a monoexponential function was applied to fit the biokinetic data. Consequently, two crucial metrics, TIAC ATPD and TIAC 2TPD, were computed for ATPD and 2TPD, respectively. To provide a benchmark, the TIAC determined via the Hänscheid method was also incorporated for comparison. The comparative analysis revealed that the percentage error between the population ATPD model and the 2TPD model was (3.97 ± 7.85)%, and for the Hänscheid model, it was (1.8 ± 7.9)%. These findings affirm that the accuracy of TIAC values derived from the 2TPD approach, leveraging prior-information fitting, is reasonably satisfactory.